(3GdbUjOI GdjJjeIs - (3CHhGdMSf Ydj Hf LHdI Hf eSde Hf YHO GdQMef GdCHfGhj , GdnYncnqhc,J (B231 (3g` s
(3ChdgG (B:s
(3gd HGdWdhd dSGFd QoO Ce gd dgG HJcde YgO? s
(3BNQgG (B:s
(3CUQjY cde Ce UQjY QOj CQOj hdjS ef GdQOi oHoO s
(3aj hUa LeGd GdLSes
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B268s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B126 s
Keywords: (3GdCOHs